PROSES PELAYANAN PEMBUATAN KARTU IDENTITAS PENDUDUK MUSIMAN DI KOTA PONTIANAK - Rahel E.21110103 (FISIP Universitas Tanjungpura, 2013)
The title of this article is the process of making service of Resident Identity Cards Seasonal in Pontianak City. Focused writing this article departing from the number of migrants from outside the city of Pontianak, especially students who do not have KIPEM, caused by complex requirements and procedure KIPEM manufacture. Research was conducted in order completed the requirements of the program completion strata 1 at the Faculty of Social and Political Sciences, University of Tanjungpura. Purpose of this study is want to describe the service process in the manufacture of KIPEM in Pontianak. Methods used in this study is qualitative descriptive research, conducted through interviews with informant. Well as supported by the observation and study documentation.The results showed that the process of making services KIPEM still felt quite complicated and convoluted by the immigrant students. Immigrant students have not fully know the procedures and requirements of making KIPEM, especially to meet the requirements of owners get KK reservoir boarding. Difficulty of obtaining reservoir due of Familly Card boarding house owner does not reside in the boarding house. This condition causes many immigrant students are reluctant to take care KIPEM complicated because the service process. On one side of the city government requires immigrants to have KIPEM student, but the other side the immigrant students find compicated to complicated the KIPEM manufacture. Keywords: Seasonal Resident Identity Card (KIPEM), Service Requirements, Service Procedure.